EVALUATION OF INTEGRATED DISEASE MANAGEMENT MODULES ON CROSSANDRA WILT INCITED BY FUSARIUM INCARNATUM (DESM.) SACC. - B. MALLAIAH; M. MUTHAMILAN (The Bioscan, 2020)
Field experiments were conducted at three villages namely Thiminayakarpatty, Sengottai and Sempatty to evaluate integrated modules for their efficacy, efficiency and consistency in management of crossandra wilt. The experiment at Thiminayakarpatty reveals that all treatments tested are effective in management of wilt incidence, but among all the treatment T8 (T. viride (Tv-9) @ 2.5kg/h as basal application at 20 DAP + soil drenching of carbendazim @ 0.1% at 30 DAP, + soil application of T. viride (Tv-9) @ 2.5 kg/ha at 50 DAP + Foliar application(FA) of P. fluorescens (Pf-18) @ 1.0 kg/ha at 70 DAP + FA of B.subtilis(Bs-10)@1.0kg/ha at 90 DAP) significantly recorded 88.3 per cent disease reduction over control followed by T12 and T2. The treat mental effect on root lesion index, indicated that among all the treatments, T12 recorded significantly higher reduction of root lesion index which accounted 70.8 per cent reduction over control, followed by T6 with root lesion index reduction of 66.7 per cent. The similar trend in disease reduction, plant growth parameters and flower yield was also observed in other field trials at Sengottai and Sempatty villages of Thamilanadu, India indicating T8 as best module for management of crossandra wilt.